1980
DOI: 10.1021/bi00542a003
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope studies on the biosynthesis of lipoic acid in Escherichia coli

Abstract: A method has been developed for the gas chromatographic-mass spectrometric (GC-MS) identification of lipoic acid in tissue. The method consists of acid hydrolysis of the tissue to free the bound lipoic acid, methylene chloride extraction of the lipoic acid, and the subsequent chemical derivatization of the lipoic acid as methyl 6,8-bis(benzylthio)octanoate prior to GC-MS analysis. By use of this method of analysis, the incorporation of deuterium into lipoic acid by Escherichia coli growing on [methyl-2H3]aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…Additional metabolic feeding studies demonstrated that in E. coli, lipoic acid biosynthesis does not involve either desaturation or hydroxylation of octanoic acid but does result in inversion of stereochemistry at C-6 (92-95). Sulfur is introduced at C-8 with racemization, in agreement with the formation of an intermediate carbon radical at C-8 (92,94,95). 8-Thiooctanoic and 6-thiooctanoic acids were both converted to lipoic acid, although 6-thiooctanoic acid was converted only 10 to 20% as efficiently as the other positional isomer (96).…”
Section: Biosynthesis Of Lipoic Acidmentioning
confidence: 81%
“…Additional metabolic feeding studies demonstrated that in E. coli, lipoic acid biosynthesis does not involve either desaturation or hydroxylation of octanoic acid but does result in inversion of stereochemistry at C-6 (92-95). Sulfur is introduced at C-8 with racemization, in agreement with the formation of an intermediate carbon radical at C-8 (92,94,95). 8-Thiooctanoic and 6-thiooctanoic acids were both converted to lipoic acid, although 6-thiooctanoic acid was converted only 10 to 20% as efficiently as the other positional isomer (96).…”
Section: Biosynthesis Of Lipoic Acidmentioning
confidence: 81%
“…Octanoic acid has been shown to be the precursor of the carbon chain (White, 1980;Parry, 1983), but neither the origin nor the mechanism whereby the sulfur atoms are inserted into the carbon chain is known. We recently investigated the function of mitochondrial ACP, which was discovered in the mitochondria of several organisms (Shintani and Ohlrogge, 1994;Schneider et al, 1997), and found that it is involved in the biosynthesis of fatty acids in mitochondria of pea and Neurospora (Wada et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although the structures and reaction mechanisms of lipoic-acid-dependent proteins have been well studied, the biosynthesis of lipoic acid has been much less studied and its mechanism has not been elucidated in any organism. In bacteria, octanoic acid or its derivatives were suggested as precursors of lipoic acid (White, 1980;Parry, 1983). This was supported by several observations of octanoylated proteins upon overexpression in Escherichia coli of gene fragments encoding the lipoyl-binding domains of E2 components from pyruvate dehydrogenase (Dardel et al, 1990;Ali et al, 1990) or upon overexpression in E. coli of mature bovine H protein of the glycine decarboxylase complex (Fujiwara et al, 1992).…”
mentioning
confidence: 88%